Empowerment Kader dan Perangkat Desa dalam Peningkatan Kapasitas Pertolongan Gawat Darurat Menggunakan Smartphone Android di Desa Pinggiran Sungai Kabupaten Banjar - Hammad, Hammad; Rizani, Khairir; Prayogi, Bisepta; Hamzani, Sulaiman; Kaila, Wafa; Rahma, Adilla Alfina; Mawaranti, Erien Febina; Rahmana, Muhamad Syeikha; Annisa, Farah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
The background of this activity is that the community in Pinggiran Sungai Village generally does not have adequate knowledge and skills in providing emergency assistance in emergency situations. The purpose of this activity is to provide training to cadres and village officials on the use of Android smartphone applications for emergency aid. The method used was training and simulation of the use of Android smartphone applications containing information and guidelines for providing cardiopulmonary resuscitation. The result of this activity is the provision of the community with knowledge and skills to provide emergency assistance for cardiac and pulmonary arrest using smartphone applications. It is expected that the community of Pinggiran Sungai Village will have better preparedness in dealing with health emergency situations.